Automated Verification of Specifications with Typestates and Access Permissions - Siminiceanu, Radu; Ahmed, Ijaz; Catano, Nestor (Electronic Communications of the EASST, 2012)
We propose an approach to formally verify Plural specifications  of concurrent programs based on access permissions and  typestates, by model-checking automatically generated abstract  state-machines. Our approach captures all possible relevant  behaviors of abstract concurrent programs implementing the  specification. We describe the formal methodology employed in  our technique and provide an example as proof of concept for the  state-machine construction rules.  We implemented the fully automated algorithm to generate and  verify models as a freely available plug-in of the Plural tool,  called Pulse.  We tested Pulse on the full specification of a  Multi Threaded Task Server commercial application and showed  that this approach scales well and is efficient in finding  errors in specifications that could not be previously detected  with the Data Flow Analysis (DFA) capabilities of Plural.